The Effect of Swimming Aerobic Physical Exercise On White Rats (Rattus Novergicus) Of the Wistar Strain That Are Obese - Vita Altamira; Evelyn Angie; Sidharta Kunardi (International Journal of Health and Pharmaceutical (IJHP), 2024)
Women are more likely to be obese and at risk of hypertension and coronary heart disease than men. Genetic factors influence it. Physical exercise can reduce obesity, especially on endothelial factors such as ET-1 and NO. This research explores the effect of swimming physical training on the expression of endothelin-1 and receptor-A in obese mouse models. This type of research is a true experiment carried out on 12 adult female Wistar rats (Rattus norvegicus) as research samples. The research procedures were carried out by caring for test animals, raising rats until they were obese, not giving treatment (control), physical training in the form of swimming exercises, and finally, examination of ET-1, ET-A, blood sugar levels, and total cholesterol levels. The data obtained was analyzed using SPSS. The research results of the normality test for the treatment group were more significant than 0.05 in the ET-1 examination of 0.315 and ET-A of 0.261. ET-1 levels were 92.5 pg/ml and ET-A levels were 62.5 pg/ml. Their blood sugar level was 167 mg/dL. The research concluded that in mouse tests, physical training was better for increasing ET-1 levels and reducing ET-A levels. Swimming and aerobics are better at lowering blood sugar levels.